Contact centre workers: loyalty, exit or... voice! Collective action in a Portuguese contact centre - Marques Alves, P. (Socioscapes. International Journal of Societies, Politics and Cultures, 2021)
In the context of a new stage of capitalism, digital work, that includes “all activities that create use-values that are objectified in digital media technologies, contents and products generated by applying digital media” (Fuchs, 2014: 352), emerged and expanded. It ranges from the production of software to the hardware assemblage, passing through the production of services, the e-commerce and digital platforms work, not forgetting the prosumers, those who consume information on the Internet but also produce it and are not paid for. In the field of the production of services, we find the call centres, which have concentrated an important share of the employment worldwide, creating what Huws (2001, 2003) calls a "cybertariat". Its expansion has been fuelled by the globalization, the service sector growth, the widespread diffusion of ICT and the productive restructuring that features the new regime of accumulation that Harvey (1989) calls "flexible accumulation”, which strongly reinforces the destructive nature of capital (Mészáros, 1997). Being an activity mediated by the technology, in it we can found the brave new world of ICT and working conditions that are typical of the past. There is evidence of a deep "real degradation of the virtual work" (Antunes and Braga, 2009). In fact, these workplaces reveal the continued application of the principles of the scientific management’s despotic regime of Taylor and Ford in terms of work organization, what contradicts the Post-Fordist thesis. On the other hand, call centres are the symbol of the network organization that characterizes the current stage of capitalism. In this logic, the widespread practice of subcontracting to rationalise costs, involving a generalized precariousness, is the norm. The changes under the flexible accumulation are not restricted to the objective sphere. The subjectivity of the workers was reached, with the apology of individualism to encourage competition between them. New hegemonic logics of domination (Burawoy, 1979) are implemented alongside with the old coercive ones and a newspeak arises in order to produce the consent of domination by the workers, leading them to cooperate with the reproduction of the capital. Under these conditions, what is the place for collective action in the call centres? Although the logics of domination implemented hinder it, through the production of conformism that leads to loyalty, and despite the individual exit attitude that prevails, hence the high levels of turnover that exist in this industry in Portugal, collective action is possible. As we will demonstrate, for it to take place it is necessary that the conditions set out by O'Sullivan and Turner (2013) are present: the existence of a common sense of injustice; to target a clear and identifiable entity, making an objective distinction between "we" and "them"; to have triggers for mobilization and a certain group identity. However, these are necessary but not sufficient conditions. These ones are the presence of a militant union in the workplace, the union’s capacity for mobilizing, the feeling of success in the action and, last but not the least, the kind of union leadership in the workplace and the possibility of an intense communication face-to-face between workers and the union.